Natural Resource Discoveries, Citizen Expectations and Household Decisions - Cust, James; Mensah, Justice Tei (World Bank, Washington, DC, 2020)
Major oil and gas discoveries are often associated with excitement and jubilation among citizens and government officials. But the extent to which discoveries substantially alter citizen expectations about economic conditions in a country remains an open question. The paper combines Afrobarometer data on household expectations on economic conditions and living standards with the announcement of oil and gas discoveries in Africa to estimate the effect of discoveries on expectations. The identification strategy exploits plausibly exogenous variation in the timing of discoveries relative to the rollout of survey interviews. The study find that discoveries increase expectations of better economic conditions and living standards by 35 and 52 percent respectively. Further, the paper finds that the overall expectations boom effect pertains only to countries with weaker institutions. The paper also provides evidence that households incorporate these expectations into their migration and fertility decisions, with fewer applications in the short run to the U.S. green card lottery and increased childbirth following discovery announcements.